Remediasi Miskonsepsi Materi Tekanan Zat Cair Pada Siswa Sma Negeri 3 Halmahera Timur Dengan Model Pembelajaran Children Learning In Science (Clis) Berbantuan Simulasi PhET - Endang Fitria (Peneliti.net, 2022)
This research was conducted to determine the effectiveness of the Children Learning in Science (CLIS) model with PhET simulations in reducing students' misconceptions about liquid pressure at XI IPA-1 SMA Negeri 3 Halmahera Timur. This type of research is a quasi pre-experimental design with one group pre-test post-test design. The population in this study were students of XI IPA-1 SMA Negeri 3 Halmahera Timur. Intact Group Random Sampling technique involving XI IPA-1. The average reduction in student misconceptions is 38.03% with a significant concept. Changes with the Mc Nemar test (????2 = 7.69 > 2 = 3.84). There is a significant ???????????????????? ???????????????????? conceptual change after remediation by applying the CLIS model using PhET simulation to reduce students' misconceptions about hydrostatic pressure. The results showed that the level of effectiveness was 0.67 (moderate). This research is expected to be used as an alternative remediation activity to reduce misconceptions in the learning process and improve student learning outcomes.